ADVANCE TREND IN NOVEL FORMULATION OF NEVIRAPINE CONJUGATED NANOEMUSION FOR ANTIRETROVIRAL MEDICATIONS (Journal of Pharmaceutical Negative Results, 2022)
The aim of this study is to formulate and evaluate the nanoemulsion of Nevirapine by use 32 factorial design to improve the oral bioavailability of nevirapine by enhance the solubility, dissolution rate and percentage transmittance. Solubility of nevirapine in different oils, surfactant and co-surfactant was determined for the screening of excipients. As based on the solubility study castor oil as oil phase, tween20 as surfactant and PEG 400 as co-surfactant were used for the NVP formulation. Nanoemulsion of nevirapine was developed using the ultrasonication method. The efficient self-emulsification region was determined by constructing with the help of ternary phase diagram having ratio 3:1, and the particle size evaluated by the zeta sizer. In vitro release profile showed more than 98 % release within 5 h which was highly significant. The particle size of F2 formulation within range found to be 131.1nm as compared to F1, F3, F4, F5, F6, F7, F8, F9, the results suggest that F2 formulation is better with regards by comparing all the evaluation parameter.